Transformasi Investasi Syariah di IAIN Manado: Analisis Minat dan Dampak Mahasiswa - Sofyan Oktavian Tubagus (Komunitas Dosen Indonesia, 2024)
This study investigates Sharia investment management strategies that can increase students' interest in investing in the Sharia capital market, especially at IAIN Manado. The research method used is qualitative with secondary data analysis. The data collection process involves searching for literature related to Sharia investment management and factors that affect students' investment interest. Secondary data analyzed includes academic publications, capital market reports, and other related studies. Key results show that there is a need to improve key aspects of strategy management, such as environmental observation, strategy formulation, implementation, and evaluation and control. Factors that influence students' interest in investing include internal, social, and emotional motives. The implication of this study is the need for a holistic approach in Sharia investment management for students, with a focus on integrating more effective strategies and a deeper understanding of the factors that influence investment decisions. This study has important implications in developing a practical approach to encourage student participation in the Sharia capital market, as well as providing guidance for educational institutions and capital market participants to create an environment that supports and facilitates the Sharia investment process for students. By addressing these challenges, educational institutions and market participants can create an environment that supports Sharia-compliant investment practices among students, thereby increasing their involvement in the overall Sharia capital market.